Polymorphonuclear Leukocyte Chemotactic Activity in Rabbit Serum and Guinea Pig Serum Treated with Immune Complexes: Evidence for C5a as the Major Chemotactic Factor - Snyderman, Ralph (1970)
A number of polymorphonuclear leukocyte (PMN) chemotactic factors derived from complement components have been described. We sought to determine which of these factors accounted for the majority of PMN chemotactic activity in rabbit serum and guinea pig serum treated with preformed immune complexes. Normal rabbit sera, guinea pig sera, or rabbit sera deficient in C6 were treated with homologous antibovine serum-albumin-bovine serum-albumin complexes. Sera so treated contained one major PMN chemotactic factor which was heat-stable (56 C for 30 min), had a molecular weight of approximately 15,000, and did not require the presence of C6 for its generation. This factor appears to be analogous to C5a.